Design and Fabrication of Highly Efficient Fan-Out Elements - Herzig, Hans-Peter; Prongué, Damien; Dändliker, René (My University, 1990)
This paper reports the calculation and fabrication of periodic phase structures fan-out elements with a theoretical conversion efficiency close to 100 percent and perfect uniformity. An efficiency of 92 percent was measured for a smooth kinoform structure fabricated in photoresist by laser beam writing lithography.
Keywords: fan-out; kinoform; phase grating; Dammann grating; CGH-HOE